2006
DOI: 10.1785/0120050804
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropy in the Shallow Crust Observed around the San Andreas Fault Before and After the 2004 M 6.0 Parkfield Earthquake

Abstract: Local seismic arrays were deployed at two locations along the San Andreas fault (SAF) near Parkfield, California, before and after the 2004 M 6.0 Parkfield earthquake. Using local earthquakes we determine the anisotropic field within 1-2 km of the main trace of the SAF at the two array locations separated by 12 km. The initial array, near the SAFOD site, was deployed for six weeks in October and November 2003, and the second array, located near the town of Parkfield, was deployed for 3 months following the 28 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
56
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 35 publications
8
56
1
Order By: Relevance
“…For this reason, we interpret the changes to be related to crustal damage occurring at least in the upper 3 km, and potentially deeper down to the middle lower crust. This interpretation also does not contradict results of other recent studies of anisotropy derived from SWS along the SAF [Cochran et al, 2006;Liu et al, 2008], because we believe our observed changes result from propagation through a thin anisotropic layer of limited extent, a case that was not addressed by these previous studies.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…For this reason, we interpret the changes to be related to crustal damage occurring at least in the upper 3 km, and potentially deeper down to the middle lower crust. This interpretation also does not contradict results of other recent studies of anisotropy derived from SWS along the SAF [Cochran et al, 2006;Liu et al, 2008], because we believe our observed changes result from propagation through a thin anisotropic layer of limited extent, a case that was not addressed by these previous studies.…”
Section: Discussionsupporting
confidence: 73%
“…It is completely described by the polarization direction of the leading wave and its delay time with the orthogonally polarized lagging wave [Crampin, 1987]. Liu et al [2008] and Cochran et al [2006] performed temporal analyses of the SWS measurements with a focus on the Parkfield seismic event and were unable to detect any precursory, co-seismic or post-seismic anisotropy change. Zhang et al [2007] also produced a map of SWS anisotropy using a tomography method and found that the distribution of anisotropy in the region was relatively complex.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, anisotropy remains an appealing key of interpretation. In recent papers, Boness and Zoback [2006], Cochran et al [2006], and Liu et al [2008] studied the shear wave splitting in the San Andreas fault. They find a fast shear wave The average is made over measures at stations closer than 250 m from the fault trace.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of aligned cracks, the fast direction is associated with the crack orientation whereas the time delay is related to the density and consistency of cracks. Alternately, if anisotropy is the outcome of shear fabric, the anisotropic component depends on the direction of fabric and degree of shearing (Cochran et al 2006).…”
Section: Continental Crustmentioning
confidence: 99%